POPI (Pediatrics: Omission of Prescriptions and Inappropriate Prescriptions): Development of a Tool to Identify Inappropriate Prescribing - Prot-Labarthe, Sonia; Weil, Thomas; Angoulvant, François; Boulkedid, Rym; Alberti, Corinne; Bourdon, Olivier (PLOS ONE, 2014)
Introduction Rational prescribing for children is an issue for all countries and has been inadequately studied. Inappropriate prescriptions, including drug omissions, are one of the main causes of medication errors in this population. Our aim is to develop a screening tool to identify omissions and inappropriate prescriptions in pediatrics based on French and international guidelines. Methods A selection of diseases was included in the tool using data from social security and hospital statistics. A literature review was done to obtain criteria which could be included in the tool called POPI. A 2-round-Delphi consensus technique was used to establish the content validity of POPI; panelists were asked to rate their level of agreement with each proposition on a 9-point Likert scale and add suggestions if necessary. Results 108 explicit criteria (80 inappropriate prescriptions and 28 omissions) were obtained and submitted to a 16-member expert panel (8 pharmacists, 8 pediatricians hospital-based −50%- or working in community −50%-). Criteria were categorized according to the main physiological systems (gastroenterology, respiratory infections, pain, neurology, dermatology and miscellaneous). Each criterion was accompanied by a concise explanation as to why the practice is potentially inappropriate in pediatrics (including references). Two round of Delphi process were completed via an online questionnaire. 104 out of the 108 criteria submitted to experts were selected after 2 Delphi rounds (79 inappropriate prescriptions and 25 omissions). Discussion Conclusion POPI is the first screening-tool develop to detect inappropriate prescriptions and omissions in pediatrics based on explicit criteria. Inter-user reliability study is necessary before using the tool, and prospective study to assess the effectiveness of POPI is also necessary.